IL-21 Receptor Antagonist Inhibits Differentiation of B Cells toward Plasmablasts upon Alloantigen Stimulation - de Leur, Kitty; Dor, Frank J. M. F.; Dieterich, Marjolein; van der Laan, Luc J. W.; Hendriks, Rudi W.; Baan, Carla C. (Frontiers in Immunology, 2017)
Interaction between T follicular helper (Tfh) cells and B cells is complex and involves various pathways, including the production of IL-21 by the Tfh cells. Secretion of IL-21 results in B cell differentiation towards immunoglobulin producing plasmablasts. In patients after kidney transplantation, the formation of alloantibodies produced by donor antigen activated B cells are a major cause of organ failure. In this allogeneic response, the role of IL-21 producing Tfh cells that regulate B cell differentiation is unknown. Here, we tested in an alloantigen driven setting whether Tfh cell help signals control B cell differentiation with its dependency on IL-21. Pre transplantation patient PBMCs were FACS sorted into pure CD4posCXCR5pos Tfh cells and CD19posCD27pos memory B cells and stimulated with donor antigen in the presence or absence of an IL-21R antagonist (αIL-21R). Donor antigen stimulation initiated expression of the activation markers ICOS and PD-1 on Tfh cells, and a shift towards a mixed Tfh2 and Tfh17 phenotype. The memory B cells underwent class switch recombination (CSR) and differentiated towards IgM and IgG producing plasmablasts. In the presence of αIL-21R, a dose dependent inhibition of STAT3 phosphorylation was measured in both T and B cells. Blockade of the IL-21R did not have an effect on PD-1 and ICOS expression on Tfh cells but significantly inhibited B cell differentiation. The proportion of plasmablasts decreased by 78% in the presence of αIL-21R. Moreover, secreted IgM and IgG2 levels were significantly lower in the presence of αIL-21R. In conclusion, our results demonstrate that IL-21 produced by alloantigen activated Tfh cells controls B cell differentiation towards antibody producing plasmablasts. The IL-21R might therefore be a useful target in organ transplantation to prevent antigen driven immune responses leading to graft failure.